Spatial and Temporal Changes of Soil Microbial Communities in Field Tomato Production as Affected by Anaerobic Soil Disinfestation - Vincent, Isaac R.; Paudel, Bodh R.; Guo, Haichao; Rosskopf, Erin N.; Di Gioia, Francesco; Hong, Jason C.; McNear, David H.; Xu, Nan; Anrecio, Lucas; Colee, James; Zhao, Xin (Frontiers in Sustainable Food Systems, 2022)
Anaerobic soil disinfestation (ASD) has been demonstrated as an effective alternative to pre-plant chemical soil fumigation (CSF) commonly used to control soilborne pathogens. However, the ASD effects on spatial and temporal changes in soil microbial communities remain poorly understood in production systems with low soilborne disease pressure. The objective of this study was to assess the influence of ASD treatments on soil microbial community composition at different soil depths during the spring tomato production season in Florida. Soil treatments included ASD using 6.9 m3 ha−1 of molasses with 11 Mg ha−1 of composted poultry litter (CPL) (ASD0.5), ASD with 13.9 m3 ha−1 of molasses and 22 Mg ha−1 CPL (ASD1.0), and chemical soil fumigation (CSF) using a mixture of 1,3-dichloropropene and chloropicrin. Soil microbial community composition was measured at soil depths of 0–15 and 15–30 cm using phospholipid fatty acid (PLFA) analysis at 0, 36, 76, and 99 days after transplanting (DAT). Fatty acid methyl esters were categorized into biomarker groups including total microbial biomass (TMB), G+ bacteria (G+), G− bacteria (G−), actinomycetes (Actino), arbuscular mycorrhizal fungi (AMF), protozoa, and general fungi (F). Soil concentrations of G+, Actino, F, AMF, and the ratio of F:bacteria (B) were significantly impacted by a soil treatment × soil depth × sampling time three-way interaction. All the microbial biomarkers were significantly affected by soil treatment × sampling depth two-way interactions except for protozoa and F:B ratio. Concentrations of TMB, Actino, AMF, F, G+, and G− bacteria were significantly increased in ASD treated soils at both 0–15 and 15–30 cm soil depths across different sampling times compared with CSF. In addition, the concentrations of G+ and G− bacteria, AMF, F, and TMB were higher at 0–15 vs. 15–30 cm soil depth under ASD treatments, whereas no soil depth differences were observed in CSF. Discriminant analysis further confirmed that soil microbial community composition was distinctly different in CSF compared with ASD treatments. The soil microbial profile was well-differentiated between the two soil depths under ASD treatments but not in CSF, while the enhancement of PLFA biomarkers by ASD decreased with increasing soil depth.